Older Persons in Southeast Asia : An Emerging Asset - Ananta, Aris; Arifin, Evi Nurvidya (Book collections on Project MUSE., 2009)
The rapid Asian fertility transitions of the last few decades will lead to population ageing in the coming decades in one country after another. Societies can choose how they will respond to the rising share of the elderly, but there is no choice about the inevitable demographic trend. In this important volume, ably edited by Evi Nurvidya Arifin and Aris Ananta, demographers, economists, sociologists, and anthropologists analyse the implications of population ageing for family and community ... The rapid Asian fertility transitions of the last few decades will lead to population ageing in the coming decades in one country after another.